Effect of home-based pulmonary rehabilitation on functional capacity in people with idiopathic pulmonary fibrosis—a systematic review protocol - Revati Amin (BMC, 2021)
Abstract Background Idiopathic pulmonary fibrosis (IPF) is one of the common types of interstitial lung disease having high prevalence and mortality worldwide. As a result of patient-centred hindering factors of adherence to centre-based pulmonary rehabilitation (PR), home-based PR is an alternate mode of rehabilitating individuals with IPF. This systematic review will evaluate the effectiveness of unsupervised home-based PR on functional capacity and health-related quality of life (HRQoL) in individuals with IPF. Methods Clinically stable, high resolution computed tomography and physician diagnosed IPF participants having modified Medical Research Council score below 5 will be considered for the systematic review. Studies involving home-based PR as an intervention to treat individuals with IPF will be considered. Randomised controlled trials and quasi-randomised studies (with two groups followed up) are eligible to be included. Outcomes of our interest are functional capacity (6-min walk distance, shuttle walk test and incremental shuttle walk test) and secondary outcome measure would include assessment of quality of life and adverse effects of intervention. Electronic databases such as SCOPUS, Medline (PubMed and Web of Science), PEDRo and CINAHL will be searched using database specific terms. Additionally, forward and backward citations of included studies will be searched to identify potential records. Two review authors, independently, will conduct the screening, data extraction using a customised standard tool, and critical appraisal using Cochrane Risk of Bias 2 tool of included studies. If data permits, meta-analysis will be conducted. In case of substantial heterogeneity, we will do a narrative synthesis. Subgroup analysis will be undertaken based on various contextual and interventional factors. Discussion This review will provide comprehensive evidence on the effectiveness of unsupervised home-based PR to physiotherapists, policy makers and researchers who are interested in IPF management. Findings from this review may guide the development and evaluation of more robust evidence based home-based PR that aimed to improve functional capacity among people with IPF. Systematic review registration PROSPERO CRD42020213883.